Aspects of persuasive language in selected speeches of Mahathir Mohamad - Alkhirbash, Abdulrahman; Paramasivam, Shamala; Ahmad, Abd. Mua'ti @ Zamri (Universiti Putra Malaysia Press, 2014)
The present study examines selected speeches of a non-Western leading politician as an attempt to widen the scope of rhetorical studies from different cultures and to address the lack of studies from non-Western societies. The study conducts a rhetorical analysis of selected speeches of Mahathir Mohamad (the fourth Prime Minister of Malaysia) to identify and interpret his language use as a means to persuade his audience to accept or follow a specific course of action. This study explores logos, ethos, and pathos as a means of persuasion demonstrating how they are utilized by Mahathir Mohamad to influence his audience. The findings revealed that logical, ethical and emotional proofs were used for this purpose. Together logos and pathos projected Mahathir’s ethos, that is, his credibility as a person, as a persuasive mean. Supportive rhetorical techniques such as examples, parallelisms, rhetorical questions and metaphors were used to enhance Mahathir’s argument and to add clarity and conciseness to the argument.